Efek Culture dan Self Identification Terhadap Memorable Tourism Experience - Faidah, Deyani; Savitri, Citra; Faddila, Syifa Pramudita (Forum Kerjasama Pendidikan Tinggi, 2025)
Tourism is one of the supporters of an increase in the economy of a region. Karawang is a district that has such beautiful nature, many people visit Saung Koffie Hideung Karawang which raises the question of why many people want to visit and enjoy coffee at Saung Koffie Hideung Karawang. This study aims to determine the effect of culture and self identification on memorable tourism experience at Saung Koffie Hideung Sempur in Karawang. The sample was obtained using non probability sampling, data as many as 177 respondents were taken from distributing questionnaires and processed using PLS-based SEM. This study found that the P values of culture on MTE are 0.00, P values of culture on self identification are 0.00 and P values of self identification on MTE are 0.023, indicating that each variable has a significant influence. This study indicates that culture and self identification are important reasons for creating a memorable tourism experience to determine consumer behavior after visiting tourist attractions. In addition, this study found new findings that women also have the habit of drinking coffee and traveling.